Theodore Metochites On Philosophers’ Irony - Domaradzki, Mikołaj (Peitho. Examina Antiqua, 2014)
The present article offers the first Polish translation of Theodore Metochites’ important essay on the philosophers’ use and abuse of irony. The translation is preceded by an introduction which briefly presents the author of the Miscellanea philosophica et historica, upon which it reconstructs the argument of essay 8 and provides an assessment of Metochites’ account of irony.